Exploring Turnover Intentions and Work Engagement: A Mediation-Moderation Approach in the Malaysian Hospitality Industry - Anantha Raj A. Arokiasamy; Jayaraman Krishnaswamy; Philip Michael Ross Smith (ASEAN Journal on Hospitality and Tourism, 2021)
In the hospitality industry, staff turnover is a big problem. The aim of this paper is to explain how, using career construction theory (CCT), turnover intentions are linked to work engagement. An analysis of 36 independent star-rated hotels in Peninsular Malaysia finds that the root cause is orientation to happiness (OTH). OTH found a negative association between work engagement and employee attrition intentions in the report. Furthermore, perceived organizational support (POS) was established as a major boundary condition, with lower levels of POS resulting in a poorer mediated relationship. This study’s theoretical and practical results would benefit the hospitality industry.